Associations of comprehensive dietary antioxidant index with postmenopausal femur bone mineral density and osteoporosis: data from the national health and nutrition examination survey - Sun, Jianbo; Wang, Jie; Hu, Wu; Huang, He; Zhao, Hongmou (Frontiers in Nutrition, 2025)
ObjectivesThe study aimed to explore associations of the comprehensive dietary antioxidant index (CDAI) with femur bone mineral density (BMD) and risk of osteoporosis in American postmenopausal women.MethodsA total of 2,862 participants from the National Health and Nutrition Examination Survey were included in this study. The relationship between the CDAI and femur BMD was assessed via weighted multivariate linear regression model. The odds ratios (ORs) and 95% confidence intervals (95% CIs) for the association between the CDAI and the risk of osteoporosis was assessed by weighted logistic regression model. Moreover, the nonlinear relationship was also characterized by smooth curve fitting and weighted generalized additive model. The two-piecewise linear regression models and a recursive algorithm were used to find the inflection points.ResultsAfter adjusting all covariates, the weighted multivariable linear regression models demonstrated that the CDAI was positively correlated with femur BMD. Moreover, there were nonlinear relationships between CDAI and risk of osteoporosis. In the age below 70 years, the risk of osteoporosis decreased to 60.6 and 92.2% with each unit increase in CDAI value before and after the inflection point (−2.268), respectively. In the 70 years or older, the risk of osteoporosis decreased to 80.4% with each unit increase in CDAI value before the inflection point (−1.479). The weighted logistic regression model demonstrated that compared to the first tertile of CDAI, the highest tertile of CDAI was significantly associated with a lower risk of osteoporosis, with ORs of 0.375 (95% CI 0.284, 0.495) for individuals under the age of 70, and 0.626 (95% CI 0.481, 0.814) for individuals aged 70 or above.ConclusionThe present study indicated that postmenopausal women with higher CDAI scores have a lower risk of osteoporosis. In addition, there is a non-linear relationship between CDAI and the risk of osteoporosis. This finding suggests that the adoption of a comprehensive antioxidant dietary structure represented by high CDAI scores may have a positive impact on the prevention and management of osteoporosis in postmenopausal women. Particularly for those with lower CDAI scores, early screening and intervention for osteoporosis may be necessary.